Safe and effective implantation and use of vagal nerve stimulation in new-onset refractory status epilepticus in early pregnancy: a case report - Jindal, Malaika; Delaj, Laura; Winston, Joel; Goel, Rishu; Bhatti, Sadia; Angelova-Chee, Milena; Selway, Richard; Mantoan Ritter, Laura (Frontiers in Neurology, 2023)
Introduction: The management of new-onset refractory status epilepticus (NORSE) in pregnancy may be complicated by anti-seizure medication (ASM) polytherapy-associated teratogenicity. We aim to demonstrate the safety and efficacy of vagal nerve stimulation (VNS) in a pregnant patient presenting with NORSE. Case description: A 30-year old female, at 5-weeks’ gestation presented with drug-refractory myoclonic status epilepticus, responsive only to high levels of anaesthetic agents. The severity of seizures did not allow extubation, and the patient remained ventilated and sedated. VNS was implanted 26 days after seizure onset. The immediate post-operative output was 0.25mA, which was rapidly titrated up to 0.5mA the next morning, and to 0.75mA that afternoon. This was further increased to 1.0mA on 3rd day post-operation, and to 1.25mA 7 days post-op. Myoclonic jerks diminished significantly 7 days post-op, allowing extubation. 20 days after VNS implantation, no myoclonic jerks were observed. There was also a notable neurological improvement including increased alertness and mobility, and ability to obey commands. Drug overdose was subsequently found to be the most likely aetiology of her NORSE. An early pregnancy assessment 17 days after VNS implantation showed a normally sited pregnancy, normal foetal heart activity and crown-rump length. The patient remained seizure free, gained functional independence and delivered a premature but otherwise healthy baby at 33 weeks’ gestation Conclusion: NORSE is challenging to manage, further compounded in pregnancy due to the teratogenicity of ASMs and ASM polytherapy. This is the first case-study to report the safe implantation and use of VNS during the first trimester of pregnancy for the management of NORSE.